Study of Coulomb collisions and magneto-ionic propagation effects on incoherent scatter radar measurements at Jicamarca - Milla, Marco (2010)
In this dissertation, Coulomb collisions and magnetoionic propagation effects on the incoherent scatter radar measurements have been studied and analyzed in detail. The present study aims at modeling radar observations of the equatorial ionosphere carried out at the Jicamarca Radio Observatory (Lima, Peru) using antenna beams pointed perpendicular to the Earth’s magnetic field B.